2004
DOI: 10.1007/s10157-004-0292-0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-induced inflammation of the kidneys: results from human studies, animal models, and tissue-culture studies

Abstract: Calcium oxalate (CaOx), calcium phosphate (CaP), and uric acid or urate are the most common crystals seen in the kidneys. Most of the crystals evoke an inflammatory response leading to fibrosis, loss of nephrons, and eventually to chronic renal failure. Of the three, CaOx monohydrate is the most reactive, whereas some forms of CaP do not evoke any discernible response. Reactive oxygen species are produced during the interactions between the crystals and renal cells and are responsible for the various cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
211
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(229 citation statements)
references
References 127 publications
12
211
1
5
Order By: Relevance
“…83 Crystal deposition in the kidneys can induce tubulointerstitial damage and inflammation, leading to fibrosis, loss of nephrons, and chronic renal failure. 84 In vitro studies have demonstrated that renal brush border MVs B100 nm in diameter, 85 can induce and promote CaOx crystallization. 86 It is not known whether such MVs also initiate CaP or urate crystal stones.…”
Section: Cancersmentioning
confidence: 99%
“…83 Crystal deposition in the kidneys can induce tubulointerstitial damage and inflammation, leading to fibrosis, loss of nephrons, and chronic renal failure. 84 In vitro studies have demonstrated that renal brush border MVs B100 nm in diameter, 85 can induce and promote CaOx crystallization. 86 It is not known whether such MVs also initiate CaP or urate crystal stones.…”
Section: Cancersmentioning
confidence: 99%
“…28. Transgenic mice showed that the overexpression of mIL-20R1a facilitated the accumulation of calcium in renal tubules.…”
Section: Resultsmentioning
confidence: 99%
“…28 In response to CaOx exposure, renal epithelial cells produce a variety of cytokines and chemoattractants to recruit immune (Figures 7a and b), whereas IL-6 transcripts were increased only in mIL-20R1a-treated TKPTS cells (Po0.05) ( Figure 7B). The expression of TNF-a, MCP-1 and RANTES in CaOx-exposed M-1 cells and that of IL-6, TNF-a, MCP-1 and RANTES in CaOx-exposed TKPTS cells further increased after 4 h of mIL-20R1a treatment (Po0.05) (Figure 7a and b).…”
Section: Mil-20r1a Treatment Of Renal Epithelial Cells Increased Caoxmentioning
confidence: 99%
See 2 more Smart Citations